mirror of
https://github.com/kalmarek/GroupRings.jl.git
synced 2024-12-28 02:40:28 +01:00
use GroupOrNCRing[Elem]
in AbstractAlgebra Rings are not groups
This commit is contained in:
parent
fbd7b940e9
commit
af1ca3e6e7
@ -1,7 +1,7 @@
|
||||
module GroupRings
|
||||
|
||||
using AbstractAlgebra
|
||||
import AbstractAlgebra: Group, GroupElem, Ring, RingElem, parent, elem_type, parent_type, addeq!, mul!
|
||||
import AbstractAlgebra: Group, NCRing, NCRingElem, parent, elem_type, parent_type, addeq!, mul!
|
||||
|
||||
using SparseArrays
|
||||
using LinearAlgebra
|
||||
@ -9,13 +9,16 @@ using Markdown
|
||||
|
||||
import Base: convert, show, hash, ==, +, -, *, ^, //, /, length, getindex, setindex!, eltype, one, zero
|
||||
|
||||
GroupOrNCRing = Union{AbstractAlgebra.Group, AbstractAlgebra.NCRing}
|
||||
GroupOrNCRingElem = Union{AbstractAlgebra.GroupElem, AbstractAlgebra.NCRingElem}
|
||||
|
||||
###############################################################################
|
||||
#
|
||||
# GroupRings / GroupRingsElem
|
||||
#
|
||||
###############################################################################
|
||||
|
||||
mutable struct GroupRing{Gr<:Group, T<:GroupElem} <: Ring
|
||||
mutable struct GroupRing{Gr<:GroupOrNCRing, T<:GroupOrNCRingElem} <: NCRing
|
||||
group::Gr
|
||||
basis::Vector{T}
|
||||
basis_dict::Dict{T, Int}
|
||||
@ -39,7 +42,7 @@ mutable struct GroupRing{Gr<:Group, T<:GroupElem} <: Ring
|
||||
end
|
||||
end
|
||||
|
||||
mutable struct GroupRingElem{T, A<:AbstractVector, GR<:GroupRing} <: RingElem
|
||||
mutable struct GroupRingElem{T, A<:AbstractVector, GR<:GroupRing} <: NCRingElem
|
||||
coeffs::A
|
||||
parent::GR
|
||||
|
||||
@ -131,13 +134,13 @@ function (RG::GroupRing{<:AbstractAlgebra.NCRing})(i::Int, T::Type=Int)
|
||||
return elt
|
||||
end
|
||||
|
||||
function (RG::GroupRing)(g::GroupElem, T::Type=Int)
|
||||
function (RG::GroupRing)(g::GroupOrNCRingElem, T::Type=Int)
|
||||
result = RG(T)
|
||||
result[RG.group(g)] = one(T)
|
||||
return result
|
||||
end
|
||||
|
||||
function (RG::GroupRing{Gr,T})(V::Vector{T}, S::Type=Int) where {Gr<:Group, T<:GroupElem}
|
||||
function (RG::GroupRing{Gr,T})(V::Vector{T}, S::Type=Int) where {Gr, T}
|
||||
res = RG(S)
|
||||
for g in V
|
||||
res[g] += one(S)
|
||||
@ -181,7 +184,7 @@ function getindex(X::GroupRingElem, n::Int)
|
||||
return X.coeffs[n]
|
||||
end
|
||||
|
||||
function getindex(X::GroupRingElem, g::GroupElem)
|
||||
function getindex(X::GroupRingElem, g::GroupOrNCRingElem)
|
||||
return X.coeffs[parent(X).basis_dict[g]]
|
||||
end
|
||||
|
||||
@ -189,7 +192,7 @@ function setindex!(X::GroupRingElem, value, n::Int)
|
||||
X.coeffs[n] = value
|
||||
end
|
||||
|
||||
function setindex!(X::GroupRingElem, value, g::GroupElem)
|
||||
function setindex!(X::GroupRingElem, value, g::GroupOrNCRingElem)
|
||||
RG = parent(X)
|
||||
if !(g in keys(RG.basis_dict))
|
||||
g = (RG.group)(g)
|
||||
@ -525,8 +528,8 @@ end
|
||||
|
||||
reverse_dict(iter) = reverse_dict(Int, iter)
|
||||
|
||||
function create_pm(basis::Vector{T}, basis_dict::Dict{T, Int},
|
||||
limit::Int=length(basis); twisted::Bool=false, check=true) where {T<:GroupElem}
|
||||
function create_pm(basis::AbstractVector{T}, basis_dict::Dict{T, Int},
|
||||
limit::Int=length(basis); twisted::Bool=false, check=true) where T
|
||||
product_matrix = zeros(Int, (limit,limit))
|
||||
Threads.@threads for i in 1:limit
|
||||
x = basis[i]
|
||||
@ -543,7 +546,7 @@ function create_pm(basis::Vector{T}, basis_dict::Dict{T, Int},
|
||||
return product_matrix
|
||||
end
|
||||
|
||||
create_pm(b::Vector{T}) where {T<:GroupElem} = create_pm(b, reverse_dict(b))
|
||||
create_pm(b::AbstractVector{<:GroupOrNCRingElem}) = create_pm(b, reverse_dict(b))
|
||||
|
||||
function check_pm(product_matrix, basis, twisted=false)
|
||||
idx = findfirst(product_matrix' .== 0)
|
||||
|
110
test/runtests.jl
110
test/runtests.jl
@ -9,7 +9,7 @@ using SparseArrays
|
||||
@testset "Constructors: PermutationGroup" begin
|
||||
G = PermutationGroup(3)
|
||||
|
||||
@test isa(GroupRing(G), AbstractAlgebra.Ring)
|
||||
@test isa(GroupRing(G), AbstractAlgebra.NCRing)
|
||||
@test isa(GroupRing(G), GroupRing)
|
||||
|
||||
RG = GroupRing(G)
|
||||
@ -115,6 +115,20 @@ using SparseArrays
|
||||
@test string(-a) == " - 2() - 1(1,2,3)"
|
||||
|
||||
@test length(a) == 2
|
||||
|
||||
@testset "RSL(3,Z)" begin
|
||||
N = 3
|
||||
halfradius = 2
|
||||
M = MatrixAlgebra(zz, N)
|
||||
E(M, i,j) = (e_ij = one(M); e_ij[i,j] = 1; e_ij)
|
||||
S = [E(M, i,j) for i in 1:N for j in 1:N if i≠j]
|
||||
S = unique([S; inv.(S)])
|
||||
E_R, sizes = Groups.generate_balls(S, radius=2*halfradius)
|
||||
E_rdict = GroupRings.reverse_dict(E_R)
|
||||
pm = GroupRings.create_pm(E_R, E_rdict, sizes[halfradius]; twisted=true);
|
||||
|
||||
@test GroupRing(M, E_R, E_rdict, pm) isa GroupRing
|
||||
end
|
||||
end
|
||||
|
||||
@testset "Arithmetic" begin
|
||||
@ -153,7 +167,7 @@ using SparseArrays
|
||||
@test isa(b//4, GroupRingElem)
|
||||
@test eltype(b//4) == Rational{Int}
|
||||
|
||||
@test isa(b//big(4), RingElem)
|
||||
@test isa(b//big(4), NCRingElem)
|
||||
@test eltype(b//(big(4)//1)) == Rational{BigInt}
|
||||
|
||||
@test isa(a//1, GroupRingElem)
|
||||
@ -208,18 +222,18 @@ using SparseArrays
|
||||
@test supp(z) == parent(z).basis
|
||||
@test supp(RG(1) + RG(perm"(2,3)")) == [G(), perm"(2,3)"]
|
||||
@test supp(a) == [perm"(3)", perm"(2,3)", perm"(1,2,3)"]
|
||||
|
||||
|
||||
end
|
||||
|
||||
|
||||
@testset "HPC multiplicative operations" begin
|
||||
|
||||
|
||||
G = PermutationGroup(5)
|
||||
RG = GroupRing(G, cachedmul=true)
|
||||
RG2 = GroupRing(G, cachedmul=false)
|
||||
|
||||
|
||||
Z = RG()
|
||||
W = RG()
|
||||
|
||||
|
||||
for g in [rand(G) for _ in 1:30]
|
||||
X = RG(g)
|
||||
Y = -RG(inv(g))
|
||||
@ -227,26 +241,26 @@ using SparseArrays
|
||||
X[rand(G)] += rand(1:3)
|
||||
Y[rand(G)] -= rand(1:3)
|
||||
end
|
||||
|
||||
@test X*Y ==
|
||||
RG2(X)*RG2(Y) ==
|
||||
|
||||
@test X*Y ==
|
||||
RG2(X)*RG2(Y) ==
|
||||
GroupRings.mul!(Z, X, Y)
|
||||
|
||||
|
||||
@test Z.coeffs == GroupRings.GRmul!(W.coeffs, X.coeffs, Y.coeffs, RG.pm) == W.coeffs
|
||||
@test (2*X*Y).coeffs ==
|
||||
@test (2*X*Y).coeffs ==
|
||||
GroupRings.fmac!(W.coeffs, X.coeffs, Y.coeffs, RG.pm) ==
|
||||
GroupRings.mul!(2, X*Y).coeffs
|
||||
end
|
||||
end
|
||||
end
|
||||
|
||||
|
||||
@testset "SumOfSquares in group rings" begin
|
||||
∗ = star
|
||||
|
||||
|
||||
G = FreeGroup(["g", "h", "k", "l"])
|
||||
S = G.(G.gens)
|
||||
S = [S; inv.(S)]
|
||||
|
||||
|
||||
ID = G()
|
||||
RADIUS=3
|
||||
@time E_R, sizes = Groups.generate_balls(S, ID, radius=2*RADIUS);
|
||||
@ -254,14 +268,14 @@ using SparseArrays
|
||||
E_rdict = GroupRings.reverse_dict(E_R)
|
||||
pm = GroupRings.create_pm(E_R, E_rdict, sizes[RADIUS]; twisted=true);
|
||||
RG = GroupRing(G, E_R, E_rdict, pm)
|
||||
|
||||
|
||||
g = RG.basis[2]
|
||||
h = RG.basis[3]
|
||||
k = RG.basis[4]
|
||||
l = RG.basis[5]
|
||||
G = (1-RG(g))
|
||||
@test G^2 == 2 - RG(g) - ∗(RG(g))
|
||||
|
||||
|
||||
G = (1-RG(g))
|
||||
H = (1-RG(h))
|
||||
K = (1-RG(k))
|
||||
@ -271,59 +285,59 @@ using SparseArrays
|
||||
|
||||
X = (2 - ∗(RG(g)) - RG(h))
|
||||
Y = (2 - ∗(RG(g*h)) - RG(k))
|
||||
|
||||
|
||||
@test -(2 - RG(g*h) - ∗(RG(g*h))) + 2G^2 + 2H^2 == X^2
|
||||
@test (2 - RG(g*h) - ∗(RG(g*h))) == GH^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 2GH^2 + 2K^2 == Y^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) +
|
||||
2(GH^2 - 2G^2 - 2H^2) +
|
||||
4G^2 + 4H^2 + 2K^2 ==
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) +
|
||||
2(GH^2 - 2G^2 - 2H^2) +
|
||||
4G^2 + 4H^2 + 2K^2 ==
|
||||
Y^2
|
||||
|
||||
|
||||
@test GH^2 - 2G^2 - 2H^2 == - X^2
|
||||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 4G^2 + 4H^2 + 2K^2 == 2X^2 + Y^2
|
||||
|
||||
|
||||
@test GH^2 == 2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2
|
||||
@test KL^2 == 2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test KL^2 == 2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2*GH^2 + 2*KL^2 ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2) +
|
||||
2(2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2) ==
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2) +
|
||||
2(2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2) +
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2G^2 + 2H^2) +
|
||||
2(2K^2 + 2L^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2 +
|
||||
2(2 - ∗(RG(g)) - RG(h))^2 +
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2 +
|
||||
2(2 - ∗(RG(g)) - RG(h))^2 +
|
||||
2(2 - ∗(RG(k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2 - ∗(RG(g*h*k)) - RG(g*h*k)) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||||
|
||||
@test 2 - ∗(RG(g*h*k)) - RG(g*h*k) ==
|
||||
|
||||
@test 2 - ∗(RG(g*h*k)) - RG(g*h*k) ==
|
||||
2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2(2GH^2 + 2K^2) + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 +
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 +
|
||||
2(2 - ∗(RG(g*h)) - RG(k))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
8G^2 + 8H^2 + 4K^2 + 2L^2 ==
|
||||
(2 - ∗(RG(g*h*k)) - RG(l))^2 + 2(2 - ∗(RG(g*h)) - RG(k))^2 + 4(2 - ∗(RG(g)) - RG(h))^2
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||||
2GH^2 + 2KL^2 == (2 - ∗(RG(g*h)) - RG(k*l))^2
|
||||
|
||||
|
||||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2(2G^2 + 2H^2) + 2(2K^2 + 2L^2) ==
|
||||
(2 - ∗(RG(g*h)) - RG(k*l))^2 + 2(2 - ∗(RG(k)) - RG(l))^2 + 2(2 - ∗(RG(g)) - RG(h))^2
|
||||
end
|
||||
|
Loading…
Reference in New Issue
Block a user